The Addictive Model of Self-Harming (Non-suicidal and Suicidal) Behavior - Blasco-Fontecilla, Hilario; Fernández-Fernández, Roberto; Colino, Laura; Fajardo, Lourdes; Perteguer-Barrio, Rosa; de Leon, Jose (Frontiers in Psychiatry, 2016)
Introduction: Behavioral addictions such as gambling, sun-tanning, shopping, internet use, work, exercise, or even love and sex are frequent, and share many characteristics and common neurobiological and genetic underpinnings with substance addictions (i.e., tolerance, withdrawal, and relapse). Recent literature suggests that both non-suicidal self-injury (NSSI) and suicidal behavior (SB) can also be conceptualized as addictions. The major aim of this mini review is to review the literature and explore the neurobiological and psychological mechanisms underlying the addiction to self-harming behaviors. Method: This is a narrative review. The authors performed literature searches on PubMed and Google for suicidal behavior, self-harming, addiction, and “major repeaters”. Given the scarce literature on the topic, a subset of the most closely related studies was selected. The authors also focused on three empirical studies testing the hypothesis that major repeaters (individuals with ≥5 lifetime suicide attempts) represent a distinctive suicidal phenotype, and are the individuals at risk of developing an addiction to SB. Results: The authors reviewed the concept of behavioral addictions and major repeaters, current empirical evidence testing concerning whether or not NSSI and SB can be understood as “addictions”, and the putative mechanisms underlying them. Conclusion: Our review suggests that both NSSI and SB can be conceptualized as addictions. This is relevant because if some individual’s self-harming behaviors are better conceptualized as an addiction, treatment approaches could be tailored to this addiction.